APLICACIÓN DE LA METODOLOGIA LEAN SIX SIGMA PARA EL DESARROLLO DE UN PLAN DE MEJORA PARA LA GESTION DE PROCESO EN UNA PYME DEL SECTOR METALMECÁNICO - Jimenez Clemente, Kevin Joseph (2022)
The research called Application of the Lean Six Sigma Methodology for the Development of an Improvement Plan for Process Management in a SME of the Metalworking Sector, has as its purpose the structured approach of the elements of the production process that are limiting its production capacity. The Lean Six Sigma methodology through its systematic method will allow to Define, Measure, Analyze, Improve and Control the entire production system of the company, so that the results obtained positively impact the level of productivity of the company and allow it to meet satisfactorily meet the demands of its customers through high-quality products. For this, during the implementation phases of the Lean Six Sigma methodology, tools will be applied to reduce and / or eliminate defects in the production process and allow the gathering of information for the standardization of operations, the identification of waste and optimization. of the production process. KEYWORDS: Methodology, Continuous Improvement, Process Management, SMEs, Productivity, Quality.